Administration of SCL 90 Scale for Depressive Disorders Among Self - Reffered Treatment - Seeking Drug Abusers in Tehran - Alireza Mohseni Tabrizi (Drug Control Headquarters, Research and Education Office, 2002)
The present article in the light of theoretical considerations on correlational associations between substance use and some socio -psychiatric disorders as well as findings of population - based epidemiologic studies on comorbidity of substance use disorders with some disorders such as depressive disorders, bipolar disorder, anxiety disorder, trauma and PTSD, psychosis, and other psychiatric disorders (Kidorf,1996, Clark and Heyendus, 1997, Glantz and Hartel, 2002, kessler, 1995), attempts to present and discuss the results and findings of a population-based comorbidity survey of treatment seeking drug abusers in Tehran.SCL90-R Scale for depressive and a structured interview for measuring APS (Addiction Potential Scale) were administered to 153 treatment seeking drug abusers which was drawn through a disproportionately stratified sampling before main treatment stage and at intoxication time and at the end of treatment preiod . The data utilized in the research were collected by a 8 page questionnaire composed of 13 items . The research findings based upon statistical analysis showed a significant correlational association between depressive disorders as measured by SCL90-R Scale and substance use as measured by APS (r = 0.46/ p= 0.0012 /R2 = 0.81). The research results also demonstrate that addictive behaviore has been under influence of such variables as the length of addiction, socio - economic status (SES), previous treatment seeking experiences and the type of drug used.